Preventing and reducing 'coercion' in mental health services: an international scoping review of English‐language studies. (9th February 2020) - Gooding, P.; McSherry, B.; Roper, C.
Abstract : This article discusses initiatives aimed at preventing and reducing 'coercive practices' in mental health and community settings worldwide, including in hospitals in high‐income countries, and in family homes and rural communities in low‐ and middle‐income countries. The article provides a scoping review of the current state of English‐language empirical research. It identifies several promising opportunities for improving responses that promote support based on individuals' rights, will and preferences. It also points out several gaps in research and practice (including, importantly, a gap in reviews of non‐English‐language studies). Overall, many studies suggest that efforts to prevent and reduce coercion appear to be effective. However, no jurisdiction appears to have combined the full suite of laws, policies and practices which are available, and which taken together might further the goal of eliminating coercion.